FACTORS THAT AFFECT THE PERFORMANCE OF DOCTORS AT THE HAJI HOSPITAL MEDAN, NORTH SUMATRA PROVINCE - Nasution, Ramadhani Syafitri; Harahap, Abidah; Effendy, Ismail (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Doctors have a central role in improving the quality of hospital services, especially through medical decision-making, explanation of diagnosis, and medical measures that protect patients' rights. However, the performance of inpatient doctors at Haji Medan Hospital in North Sumatra Province is still low, with an achievement of only 47% of the expected target. This condition has the potential to reduce the quality of service if not handled immediately. This study aims to analyze the factors that affect the performance of inpatients at Haji Medan Hospital. The study used a quantitative design with a cross sectional approach. The sample consisted of 74 doctors with a total sampling technique. Data analysis was carried out through univariate, bivariate, and multivariate tests using logistic regression. The results showed that workload (p=0.015), work stress (p=0.008), work environment (p=0.001), incentives (p=0.003), and compensation (p<0.001) had a significant effect on physician performance. Thus, the main factors that affect the performance of doctors are aspects of workload, psychological condition, work environment support, and reward and compensation systems. These findings are expected to be input for hospital management to improve policies and create more supportive working conditions, as well as the basis for further research with broader variables.